STUDENTS’ ABILITY IN PRONOUNCE OF SPEAKING ENGLISH USED TIK-TOK APPLICATION IN ENGLISH LEARNING AT ENGLISH EDUCATION PROGRAM OF UMB - Mutiara Gani Putri; Agung Suhadi (Teaching English and Language Learning English Journal, 2024)
The purpose of this research was to know the students’ ability in pronounce of speaking English used Tik-tok application in English learning at English education program of UMB. This research was designed as descriptive qualitative method. The subject of this research were the sixth semester of English education program of Muhammadiyah Univesity of Bengkulu. The instrument of research were test by video recording. Data analysis technique taken by using Hughes’ speaking rubrics such as fluency, pronunciation, vocabulary, grammar, and detail. The result of the research was students ability in pronounce of speaking English used Tik-tok application of score obtained 3.6 score which mean that the students ability in pronounce of speaking English used Tik-tok application was good level of category. Keywords: Student’Ability, Pronunciation, Speaking English, Tik-tok Application.